Correlation of Malignancy in the Hepato-Pancreato-Biliary System with Serum Bilirubin Levels in Extrahepatic Cholestasis Patients - Rizqy Tansa; M. Iqbal Rivai; Avit Suchitra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: The incidence of hepato-pancreato-biliary system cancer is increasing worldwide, which has been recognized as a disease that is difficult to diagnose early and has a poor prognosis. No research has yet been conducted in areas with limited resources and health facilities. There is an urgent need for diagnostic methods to recommend further diagnostic modalities in the selection of curative or palliative management. Methods: Retrospective data from all cholestatic patients at Dr. M. Djamil General Hospital were collected during the period July 2020-May 2022. The data included demographic characteristics such as age, gender, preoperative, results of bilirubin fraction, and final diagnosis. Data analysis was done by bivariate and multivariate. Results: A total of 132 patients were included in this study. 35.6% of them are HPB system malignancies, with Pancreatic Adenocarcinoma being the most common diagnosis (34.4%), more in males (51.06%), and in the age group, 50 years (61.71%) is the most. Only 52.27% of patients underwent preoperative radiological imaging. Bivariate analysis showed a significant relationship between HPB system malignancies with age >50 years (p=0.024) and all bilirubin fractions (p<0.001). Multivariate analysis showed that only the bilirubin fraction was significant for the diagnosis of malignant HPB (p<0.001). Conclusion: The bilirubin fraction is a good initial indicator for predicting malignancy in the HPB system in order to increase the effectiveness of the diagnostic modality and reduce the referral duration.